Isolation of recombinant DNA clones carrying complete integrated proviruses of Moloney murine leukemia virus. - Bacheler, L (1981)
EcoRI DNA fragments from a Moloney murine leukemia virus (M-MuLV)-infected mouse fibroblast line (M-MuLV clone A9) were cloned in lambda phage Charon 4A cloning vector to derive clones containing integrated M-MuLV proviral DNA. A 10- to 16-megadalton class of EcoRI fragments was chosen for cloning, based on (i) its ability to induce XC-positive virus upon transfection of NIH/3T3 cells, and (ii) its content of a 0.8-megadalton viral KpnI fragment diagnostic for M-MuLV. Six recombinant DNA clones were isolated which contain a complete M-MuLV provirus, as judged by (i) restriction endonuclease mapping and (ii) the fact that all of the clones gave rise to XC-positive, NB-tropic virus upon DNA infection in NIH/3T3 cells. The sizes of the inserts were 12.0 (for three clones) or 12.5 megadaltons (for three clones). Restriction mapping indicated that these six clones represent five different M-MuLV proviral integrations into different cellular DNA sites.